Therapeutic challenges and new therapeutic targets for combined capillary pulmonary hypertension: a review - Lu, Ming; Wang, Baoguo; Rong, Chunyan; Wang, Yin; Zhang, Weihua (Frontiers in Medicine, 2025)
With a high frequency and a poor prognosis, combined pre-and post-capillary pulmonary hypertension (Cpc-PH) is a significant subtype of pulmonary hypertension linked to left-sided heart disease (PH-LHD). The complicated pathophysiology of Cpc-PH is primarily characterized by elevated pulmonary venous pressure leading to an increase in retrocapillary pressure, which is followed by elevated pulmonary artery pressure and a marked rise in pulmonary vascular resistance (PVR). There is currently no well-defined treatment plan for Cpc-PH, and there are numerous obstacles to overcome. In patients with Cpc-PH, the effectiveness of targeted medications for pulmonary hypertension is limited and debatable. Recent research has revealed that the prevalence and progression of Cpc-PH may be influenced by genetic factors, metabolic syndrome, oxidative stress, and fibrosis. To help doctors better manage and treat patients with Cpc-PH, this review provides a detailed description of the disease’s epidemiology, pathogenesis, diagnostic techniques, current treatment status, and potential therapeutic targets.